2019
DOI: 10.1021/acs.analchem.9b03247
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Response of Aortic Endothelial Cells under Pulsatile Flow Using a Compact Microfluidic System

Abstract: We describe a piezoelectric pumping system for studying the mechanobiology of human aortic endothelial cells (HAECs) under pulsatile flow in microfluidic structures. The system takes advantage of commercially available components, including pumps, flow sensors, and microfluidic channels, which can be easily integrated, programmed, and operated by cellular biologists. Proof-of-concept experiments were performed to elucidate the complex mechanotransduction processes of endothelial cells to pulsatile flow. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 61 publications
4
30
0
Order By: Relevance
“…Pulsatile flow also increased cell size and changed the distribution of the endothelial cell adhesion molecule CD31 and mechanical sensor PIEZO1, suggesting that EC structure is affected by pulsatile flow. Pulsation, including frequency and amplitude, plays an important role in EC protein expression and morphology 7,8 . Disturbed flow is known to affect EC behavior, including EC turnover, low density lipoprotein permeability, atherogenesis, and gene expression [40][41][42][43] .…”
Section: Endothelial Cells Differentiated Under Lqts Pulsatile Flow Ementioning
confidence: 99%
See 3 more Smart Citations
“…Pulsatile flow also increased cell size and changed the distribution of the endothelial cell adhesion molecule CD31 and mechanical sensor PIEZO1, suggesting that EC structure is affected by pulsatile flow. Pulsation, including frequency and amplitude, plays an important role in EC protein expression and morphology 7,8 . Disturbed flow is known to affect EC behavior, including EC turnover, low density lipoprotein permeability, atherogenesis, and gene expression [40][41][42][43] .…”
Section: Endothelial Cells Differentiated Under Lqts Pulsatile Flow Ementioning
confidence: 99%
“…Endothelial cells (ECs) line the lumen of blood vessels, so pulsatile flow provides a more relevant in vivo microenvironment for these ECs compared to constant flow. Numerous studies have shown that pulsatile flow and constant flow have different effects on ECs in vitro, including EC morphology and alignment 7,8 , gene expression 9, 10 , distribution of adhesion proteins 8 , cell proliferation, and apoptosis 11 . The pulsation frequency and peak amplitude of the pulsatile flow also plays an important role in EC morphology and protein expression 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…pumps 22,23 . Syringe pumps, in particular, are among the most common type of pump used for laboratory microfluidics.…”
mentioning
confidence: 99%